2013
DOI: 10.1111/jsr.12119
|View full text |Cite
|
Sign up to set email alerts
|

Sleep enhances memory consolidation in children

Abstract: SUMMARYSleep is an active state that plays an important role in the consolidation of memory. It has been found to enhance explicit memories in both adults and children. However, in contrast to adults, children do not always show a sleep-related improvement in implicit learning. The majority of research on sleep-dependent memory consolidation focuses on adults; hence, the current study examined sleep-related effects on two tasks in children. Thirty-three typically developing children aged 6-12 years took part i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 25 publications
6
51
1
Order By: Relevance
“…Motor learning also appeared to benefit from napping, but only after an extended period of sleep, including night sleep 150 . In older children, 6-12 years old, a period of sleep was also associated with the improvement of a non-word learning task and a cognitive puzzle 151 . However, the relationship between napping habits and cognitive M A N U S C R I P T…”
Section: Napping and Memory Functions In Childrenmentioning
confidence: 99%
“…Motor learning also appeared to benefit from napping, but only after an extended period of sleep, including night sleep 150 . In older children, 6-12 years old, a period of sleep was also associated with the improvement of a non-word learning task and a cognitive puzzle 151 . However, the relationship between napping habits and cognitive M A N U S C R I P T…”
Section: Napping and Memory Functions In Childrenmentioning
confidence: 99%
“…Ashworth, Hill, Karmiloff‐Smith, and Dimitriou () showed in children aged 6–12 years that performance on the Tower of Hanoi (TOH), a task that primarily involves executive functions such as planning and problem‐solving, improved only across a period that included sleep but not across a similar period of wakefulness only. This finding suggests that sleep supports the learning of planning and problem‐solving; however, the involvement of specific sleep stages and microstructural sleep characteristics was not addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have suggested that sleeping is important for memory function,[235] the basic biological need for sleep is still uncertain. [34] Recent studies have shown that during the sleep state the glymphatic activity is significantly increased, whereas its function is suppressed during wakefulness.…”
Section: Sleepmentioning
confidence: 99%